2010
DOI: 10.1016/s1470-2045(10)70198-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pamidronate 30 mg versus 90 mg on physical function in patients with newly diagnosed multiple myeloma (Nordic Myeloma Study Group): a double-blind, randomised controlled trial

Abstract: Background: Prophylactic treatment with bisphosphonates reduces skeletal events in multiple myeloma compared with placebo. However, the toxicity associated with long-term treatment makes it important to find the lowest effective dose. The aim of this study was to compare the effect of two doses of pamidronate on health-related quality of life and skeletal morbidity in patients with newly diagnosed multjple myeloma.Methods: Multiple myeloma patients starting antimyeloma treatment were randomly assigned to month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 37 publications
0
59
0
2
Order By: Relevance
“…20 The major flaw of this study was that it was powered to show differences in quality of life and not in SREs. 20 Finally, the third study, which compared intravenous ZA with oral clodronate, found that ZA reduced the SRE risk compared to clodronate in all patients, irrespective of the presence of lytic lesions at diagnosis, but furthermore, improved overall survival (OS) by ten months in MM patients with lytic lesions at diagnosis. 21,22 These effects continued in patients who received ZA for more than two years.…”
Section: Gradementioning
confidence: 99%
“…20 The major flaw of this study was that it was powered to show differences in quality of life and not in SREs. 20 Finally, the third study, which compared intravenous ZA with oral clodronate, found that ZA reduced the SRE risk compared to clodronate in all patients, irrespective of the presence of lytic lesions at diagnosis, but furthermore, improved overall survival (OS) by ten months in MM patients with lytic lesions at diagnosis. 21,22 These effects continued in patients who received ZA for more than two years.…”
Section: Gradementioning
confidence: 99%
“…These bisphosphonates have demonstrated varying activity in SRE-prevention trials in patients with multiple myeloma, metastatic breast cancer, prostate cancer, and lung cancer (Table 1). [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] However, it should be noted that pamidronate and ZOL are the only bisphosphonates approved in the metastatic breast cancer setting in the United States. 30,31 Recently, the antiresorptive agent denosumab also gained approval in the United States for the prevention of SREs in patients with bone metastases from solid tumors, including breast cancer.…”
Section: The Burden Of Bone Metastases In Women With Advanced Breast mentioning
confidence: 99%
“…9,10 In the second, two doses of intravenous pamidronate (30 versus 90 mg) showed comparable results regarding time to skeletal-related events and survival time free of such events. 11 The limitation of this study was that it was powered to show differences in quality of life and not in skeletal-related events. 11 The third study compared intravenous (i.v.)…”
mentioning
confidence: 99%
“…11 The limitation of this study was that it was powered to show differences in quality of life and not in skeletal-related events. 11 The third study compared intravenous (i.v.) zoledronic acid with oral clodronate and showed that zoledronic acid reduced the risk of skeletalrelated events compared to clodronate in all MM patients, irrespective of the presence of lytic lesions at diagnosis, and improved overall survival by 10 months in patients with lytic lesions at diagnosis.…”
mentioning
confidence: 99%